Sosialisasi kesehatan dengan tema kiat sehat untuk menjaga konsentrasi belajar di kalangan santri Ma’had Madrasah Aliyah Negeri 2 Lamongan - Habibah, Lailatul; Faiza, Gabhiela Ghina; Prameswari, Anandayu Gita; Candra, Zaqias; Adzani, Wanasa Rahmat Akbar; Anam, Syaiful; Rahman, Linda Octaverina; Anwar, Salwa Oktarina Bahirah; Sholeh, Achmad Khozen (Maliki Interdisciplinary Journal, 2024)
Study concentration is an important factor in achieving learning success. Students, especially at Ma’had Madrasah Aliyah Negeri 2 Lamongan, often have difficulty concentrating when studying. This can hinder their learning process and achievement. Health outreach with the theme of healthy tips for maintaining study concentration among students of Ma’had Madrasah Aliyah Negeri 2 Lamongan aims to increase students’ understanding of the importance of maintaining physical and mental health in supporting the learning process. The results show that health outreach is effective in increasing students’ knowledge and awareness about healthy tips for maintaining concentration in learning. This health outreach needs to be carried out on an ongoing basis and needs to involve various parties to provide maximum benefits for students.